Opinion 2408: Alabina Dall, 1902 (Gastropoda, Cerithioidea): designation of Alaba cerithidioides Dall, 1889 as type species not approved - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has declined to use its plenary power to set aside all previous fixations of type species for Alabina Dall, 1902 prior to the designation of Alaba cerithidioides Dall, 1889 by Dall (1902).
Keywords: Nomenclature; taxonomy; ALABINIDAE; Alabina; Alaba cerithidioides; gastropods; western Atlantic